2005
DOI: 10.1634/stemcells.2005-0094
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Expansion of Human Mesenchymal Stem Cells: Choice of Serum Is a Determinant of Cell Proliferation, Differentiation, Gene Expression, and Transcriptome Stability

Abstract: Human bone marrow mesenchymal stem cells (hMSCs) represent an appealing source of adult stem cells for cell therapy and tissue engineering, as they are easily obtained and expanded while maintaining their multilineage differentiation potential. All current protocols for in vitro culture of hMSCs include fetal bovine serum (FBS) as nutritional supplement. FBS is an undesirable additive to cells that are expanded for therapeutic purposes in humans because the use of FBS carries the risk of transmitting viral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
357
4
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(385 citation statements)
references
References 41 publications
14
357
4
10
Order By: Relevance
“…The in vitro, in vivo and clinical bone‐forming capacity of ASCs in combination with various scaffold materials have been reported by many authors 14, 20, 35, 36, 37, 38, 39, 40, 41. In this series, the flow cytometric characterization of the ASCs expanded in autologous serum corresponded to previously published results for ASCs 42, 43. According to flow cytometry, and alkaline phosphatase staining results, the cells were of mesenchymal origin and had a capacity to differentiate into the osteoblastic lineage.…”
Section: Discussionsupporting
confidence: 86%
“…The in vitro, in vivo and clinical bone‐forming capacity of ASCs in combination with various scaffold materials have been reported by many authors 14, 20, 35, 36, 37, 38, 39, 40, 41. In this series, the flow cytometric characterization of the ASCs expanded in autologous serum corresponded to previously published results for ASCs 42, 43. According to flow cytometry, and alkaline phosphatase staining results, the cells were of mesenchymal origin and had a capacity to differentiate into the osteoblastic lineage.…”
Section: Discussionsupporting
confidence: 86%
“…Serum-free medium is unable to promote MSC expansion unless several recombinant human growth factors (GF) such as platelet-derived growth factor (PDGF), fibroblast growth factor (FGF), transforming growth factor (TGF)-β, and epidermal growth factor (EGF) are added to the medium. However, 1) defining the optimal amount of GF is difficult, 2) only a few GFs are licensed for therapeutic use, 3) recombinant Human-GFs are expensive, and 4) isolated GF cannot replace the different physiological functions of FBS (15)(16)(17).…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…Genome-wide transcriptome and promoter methylation studies have shown that the expressed gene profile changes on culturing MSC in vitro with increased expression of, among others, cytoskeleton proteins and downregulation of cell cycle inhibitory genes [36], which is accompanied by progressive epigenetic changes [37]. There is also evidence that relatively minor changes to the culture conditions used to expand MSC, including culture at different oxygen tensions, use of fetal calf serum versus autologous serum, use of platelet lysate, or addition of growth factors (e.g., FGF2 or platelet-derived growth factor [PDGF]), affect MSC proliferation ability as well as the rate and degree of differentiation to the osteogenic, adipogenic, and chondrogenic lineages [36,[38][39][40][41]. These functional changes are associated with differences in expressed gene profile and epigenomic state of the cells [36,[38][39][40][41].…”
Section: Can In Vitro Culture Convert Germline Stem/progenitor Cells mentioning
confidence: 99%